Hamiltonian formulation of the full vectorial Helmholtz equation for modeling the interaction between ME composites and optical _ber immersed in electromagnetic _elds from high voltage power systems (2019)
TThis thesis deals with the proposal, analytical background and practical implementation of fiber optic based sensors for measuring electrical variables in high voltage systems. The thesis presents the physical and mathematical formulation for each of the sensing principles that were tackled in the proposition and develops the theoretical backgorund for each particular application. Three main contributions should be highlighted from the obtained results: Firstly, the formulation of the interaction characteristics with optical fibers by extending the coupled theory mode through a Hamiltonian formulation of the Helmholtz equation to account for transverse perturbations into the propagation characteristics of propagating light. Secondly, the proposition of a numerical method for predicting the magnetic characteristics of magnetostrictive-powder/epoxy composites with arbitrary shapes. Finally, the proposition of two fiber-based sensor for sensing electric variables (magnetic field and voltage magnitudes) from high voltage systems. Proposed sensors were implemented in practice and their results were contrasted to the theoretical expected performance leading to very good agreements. Future work is proposed based on the main opportunities discovered during the analytical and practical implementation of the sensors.